Tourism Music in Mallorca: From Mallorcastyle to the Serra de Tramuntana (Global Journal of Human-Social Science, 2023)
Mallorcastyle music transmits and reproduces the lifestyle of drunken tourism of Germanic origin on the island of Mallorca It is a type of Electronic Dance Music whose music videos which we will analyse in this paper show an image of debauchery in the form of alcohol consumption nightlife pool parties and rest on the beach behaviours that appear associated with the search for sexual relations within heteropatriarchal schemes
Keywords: mallorcastyle; s'arenal; EDM; heteropatriarchal sexuality; mediterranean-ness; tourism model